Convertible Securities and Venture Capital Finance - Klaus Schmidt (Center for Economic Studies and ifo Institute (CESifo), 1999)
This paper offers a new explanation for the prevalent use of convertible securities in venture capital finance. Convertible securities can be used to endogenously allocate cash flow rights as a function of the realized quality of the project. This property can be used to mitigate the double moral hazard problem be t ween the entrepreneur and the venture capitalist. It is shown that an optimally designed convertible security outperforms any mixture of debt and equity and that it can induce both parties to invest efficiently. The result is robust to renegotiation and t o changes in the timing of investments and information flows.
Keywords: 330; Convertible securities; venture capital; corporate finance; double moral hazard; incomplete contracts